2019
DOI: 10.1002/jeab.553
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal choice and initial‐link requirement

Abstract: Pigeons (n = 14) were trained in a concurrent-chains suboptimal choice procedure that tested the effect of an increased ratio requirement in the initial links. Fixed-ratio 1 and 25 conditions were manipulated within subjects in a counterbalanced order. In all conditions, distinct terminal-link stimuli on a suboptimal alternative signaled either primary reinforcement (20% of the time) or extinction (80% of the time). On an optimal alternative, two distinct terminal-link stimuli each signaled a 50% chance of pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…However, there was a high degree of individual-subject variability in the influence of IL duration on suboptimal choice, with 3 of 5 pigeons still preferring the suboptimal alternative to some extent with longer IL durations. Pisklak et al (2019) assessed choice between a suboptimal alternative delivering food 20% of the time with differential TL stimuli and an optimal alternative delivering food 50% of the time without differential TL stimuli. The IL schedule was either an FR 1 (short duration) or an FR 25 (long duration).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there was a high degree of individual-subject variability in the influence of IL duration on suboptimal choice, with 3 of 5 pigeons still preferring the suboptimal alternative to some extent with longer IL durations. Pisklak et al (2019) assessed choice between a suboptimal alternative delivering food 20% of the time with differential TL stimuli and an optimal alternative delivering food 50% of the time without differential TL stimuli. The IL schedule was either an FR 1 (short duration) or an FR 25 (long duration).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is based on only a few experiments (i.e., Experiment 3 from Dunn & Spetch, 1990; Kendall, 1974; Zentall et al, 2017), some of which have been criticized for unorthodox procedural details (e.g., the use of dark keys as TL stimuli in Kendall, 1974). Furthermore, there is sometimes a high degree of individual-subject variability in the influence of IL duration on suboptimal choice in pigeons (e.g., Pisklak et al, 2019; Zentall et al, 2017), and longer IL durations do not always decrease suboptimal choice (e.g., Experiment 1 from Dunn & Spetch, 1990). Given such limited and inconsistent evidence, some theories do not explicitly include a role for IL duration in suboptimal choice, such as the predictive-value hypothesis (Zentall, 2016) and the associability-decay model (Daniels & Sanabria, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many recent studies have tested pigeons’ choice between signaled 20% and unsignaled 50% food as shown in Panel B of Figure 1. The key features of these procedures are FR 1 initial links (i.e., a single choice response) and FT 10-s terminal links (i.e., delays fixed at 10 s; Fortes et al, 2016, 2017, 2018; González et al, 2020b; González-Torres et al, 2020; López-Tolsa & Orduña, 2021; Macías et al, 2021; Pisklak et al, 2019b; Stagner et al, 2012; Stagner & Zentall, 2010; Zentall & Stagner, 2011). Results have consistently shown strong preference for the suboptimal (20%) alternative.…”
Section: Suboptimal Concurrent-chains Procedures and Literature Reviewmentioning
confidence: 99%